The Role of Dividend Policy as Intervening Variables on The Effect of Earning Per Share, Debt Equity Ratio and Price Book Value on Stock Price - Salim, Muhammad Agus; Pardiman, Pardiman (Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study is to analyze the role of dividend policy in mediating the effect of earnings per share, debt equity to ratio and price book value on stock prices. The sample used is a manufacturing company listed on the Indonesian stock exchange with complete financial statements for the 2015-2020 period. Data were analyzed using path analysis method using SPSS version 25 software. The results of this study indicate that earnings per share have no effect on dividend policy. Debt equity to ratio has no effect on the company’s dividend policy. Price book value has no effect on the company’s dividend policy. Dividend performance has no effect on stock prices. Earning per share has an effect on stock prices. Debt equity to ratio has an effect on stock prices. Price book value has an effect on stock prices. Dividend policy is not successful in mediating the effect of earnings per share on stock prices. Dividend policy also failed to mediate the effect of debt euqity to ratio on stock prices. Furthermore, the dividend policy also failed to mediate the effect of price book value on stock prices